THE FILM ACTOR VERSUS THE THEATER ACTOR: CAZUL GAVRILESCU (THE GAVRILESCU CASE) AND PESCUIT SPORTIV (HOOKED) - Titieni, Adrian; Rusti, Doina (European Scientific Journal, ESJ, 2014)
The article sets out from a number of studies of roles that unfold over a longer period of time, in order to analyse two concepts closely related to acting: dramatisation and authenticity. Drawing upon the semiotics of Greimas and Fontanille, our study establishes the pathemic journey of two characters – one from theatre, the other from cinema - in two works of differing artistic registers, but similar fields: Gavrilescu (The Gavrilescu Case, drama, 1996-1998 ) - and a movie character - Mihai (Hooked, movie, 2009). The conclusion is that in both situations acting demands identification with the character, as well as the construction of a simulacrum.